Voluntary (NGO) Sector’s Involvement in Health Promotion for Older Population in Europe (Epidemiology, Biostatistics, and Public Health, 2022)
Background and objective: The NGO’s (non-governmental organisations’) role in health promotion is very much praised and encouraged. The basic features of this sector, namely social participation, voluntary activity and self-help, are by default considered as beneficial for health promotion for older people. New policy approaches stimulate NGOs involvement in it. This makes questions about this involvement – its role, context and success – increasingly relevant.Method: The research is based on narrative literature review as well as interviews and consultations with informers (practitioners and experts) in selected European countries.Results: Voluntary/NGO sector increases its role as a complimentary or alternative source of health promotion for older people in Europe. Its involvement, roles and functions as well as actual significance, however, depends on a number of factors. It depends on the sustainability of funding, stability of employment, elderly participation rate and recognized availability of services. Those factors are determined by socio-economic and systemic conditions: a country-specific model of third sector, overall social attitudes towards participation and system of governance in health promotion.Conclusion: The sector’s significance is widely acknowledged, however, its impact is often only assumed rather that sufficiently assessed and proven. By its voluntary nature, the sector might not be able to address the problem of health inequalities. Also, various political and economic changes across Europe result in the change of the sector’s performance.